Characterization and Modeling of Intermetallic Phase Formation during the Joining of Aluminum and Steel in Analogy to Co-Extrusion - Bernd-Arno Behrens; Hans Jürgen Maier; Christian Klose; Hendrik Wester; Susanne Elisabeth Thürer; Norman Heimes; Johanna Uhe (Metals, 2020)
The reinforcement of light metal components with steel allows to increase the strength of the part while keeping the weight comparatively low. Lateral angular co-extrusion (LACE) offers the possibility to produce hybrid coaxial profiles consisting of steel and aluminum. In the present study, the effect of the process parameters temperature, contact pressure and time on the metallurgical bonding process and the development of intermetallic phases was investigated. Therefore, an analogy experiment was developed to reproduce the process conditions during co-extrusion using a forming dilatometer. Based on scanning electron microscopy analysis of the specimens, the intermetallic phase seam thickness was measured to calculate the resulting diffusion coefficients. Nanoindentation and energy dispersive X-ray spectroscopy measurements were carried out to determine the element distribution and estimate properties within the joining zone. The proposed numerical model for the calculation of the resulting intermetallic phase seam width was implemented into a finite element (FE) software using a user-subroutine and validated by experimental results. Using the subroutine, a numerical prediction of the resulting intermetallic phase thicknesses is possible during the tool design, which can be exploited to avoid the weakening of the component strength due to formation of wide intermetallic phase seams.